PHENOMENON OF NATIONAL IDENTIFICATION - Maxmudova, L.Yu (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
The answer and thoughts about the set the question can be found in the works and studies of Western scholars, philosophers, political scientists such as B. Anderson, M. Hroh, E. Hobsbaum, E. Smith, E. Gelner, E. Renan, Yu.V. Bromley, C. Calhoun, C. Levy-Strauss, J. Derrida, S. Huntington, M. Weber, E. Erickson, O. Bauer et al. There are concepts of nation and national; different theories and points of view regarding problems of preserving the nation and national due.